RNA-binding proteins and their role in translational regulation in plants. Issue 2 (5th August 2022) - Duarte-Conde, José Antonio; Sans-Coll, Gemma; Merchante, Catharina
Abstract: Translation is a fundamental process for life that needs to be finely adapted to the energetical, developmental and environmental conditions; however, the molecular mechanisms behind such adaptation are not yet fully understood. By directly recognizing and binding to cis -elements present in their target mRNAs, RBPs govern all post-transcriptional regulatory processes. They orchestrate the balance between mRNA stability, storage, decay, and translation of their client mRNAs, playing a crucial role in the modulation of gene expression. In the last years exciting discoveries have been made regarding the roles of RBPs in fine-tuning translation. In this review, we focus on how these RBPs recognize their targets and modulate their translation, highlighting the complex and diverse molecular mechanisms implicated. Since the repertoire of RBPs keeps growing, future research promises to uncover new fascinating means of translational modulation, and thus, of gene expression.